Anti-blocking bending-resistant abrasive paper and preparation process thereof

By using composite substrate layer, reinforced adhesive layer, self-cleaning abrasive layer and multifunctional surface coating in the sandpaper, the existing sandpaper has poor bending resistance, insufficient high temperature resistance, weak anti-blocking ability and uneven wear in complex working conditions, significantly improving the performance and service life of the sandpaper.

CN119871242AInactive Publication Date: 2025-04-25DONGGUAN AOZHONG ABRASIVES PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510170249.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In complex working conditions, existing sandpapers have problems such as failure of fracture due to poor bending resistance of the substrate layer, particle fallout caused by insufficient high temperature resistance of the adhesive layer, weak anti-blocking ability of the abrasive layer, and uneven wear of the single-layer coating design.

Method used

The composite substrate layer is used to achieve a balance of high strength and flexibility of the substrate through the blending of carbon fiber and aramid fiber, the distribution of thermally conductive ceramic particles and the embedding of shape memory alloy wires. At the same time, a modified acrylic adhesive layer reinforced by nanofillers and high thermal conductivity fillers is formed with high adhesion and high heat dissipation properties. The composite abrasive particles designed with plasma treatment and hydrophobic coating are constructed to build a self-cleaning abrasive layer and form a multifunctional surface coating through a chemical vapor deposition process.

Benefits of technology

It significantly improves the bending resistance of sandpaper and solves the problem of traditional sandpaper prone to breaking and fatigue failure in complex surface processing. At the same time, the high temperature resistance of the adhesive layer is enhanced, the anti-blocking ability of the abrasive layer is improved, the service life of the sandpaper is extended, and the anti-blocking and durability of the surface coating is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119871242A_ABST
    Figure CN119871242A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of grinding materials and grinding tools, and discloses anti-blocking bending-resistant abrasive paper, the abrasive paper comprises a base material layer, a binder layer, an abrasive material layer and a surface coating, the base material layer is made of a carbon fiber and aramid fiber blended material, and the base material layer is prepared by compounding 2-5 parts by weight of carbon fiber and aramid fiber blended material, 0.5-1.5 parts by weight of heat-conducting ceramic particles and 0.2-0.8 part by weight of shape memory alloy wires; the binder layer is composed of 4-8 parts of modified acrylate resin, 0.1-0.3 part of nano filler and 1-2 parts of high-thermal-conductivity filler, the invention further provides a preparation technology of the anti-blocking bending-resistant abrasive paper, and the preparation technology comprises the following steps that the base material layer is prepared; coating a binder layer; attaching abrasive particles; forming a surface coating; and a post-treatment process. Through the design of the composite base material, the nanofiller reinforced binder, the plasma treated abrasive particles and the multi-layer coating, efficient grinding, long service life and anti-blocking performance of the abrasive paper under complex working conditions are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of abrasive materials and grinding tools, in particular to anti-clogging and bending-resistant sandpaper and a preparation process thereof. Background Art

[0002] In modern manufacturing, grinding is a crucial process. Whether it is the surface treatment of high-precision parts or the polishing and finishing of complex curved workpieces, sandpaper is needed to achieve efficient material removal and improve the finish. Especially in the fields of aerospace, automobile manufacturing and electronic equipment, the performance requirements for sandpaper are more stringent.

[0003] In the prior art, a variety of sandpaper designs have been optimized for different needs. For example, the tensile properties of sandpaper are improved by strengthening the material strength of the substrate layer. This method shows good durability in conventional grinding. In addition, the traditional binder layer is mainly resin-based, which can provide a stable adhesion effect of abrasive particles and ensure the grinding efficiency of sandpaper in short-term use. Improvements to abrasive particles, such as the use of high-hardness zirconium oxide materials, have also significantly improved the cutting ability of sandpaper. In terms of surface coating, some sandpapers reduce the problem of particle shedding through a single-layer protective coating and show certain wear resistance under low-speed dry grinding conditions. These existing technical solutions provide basic support for improving the performance of sandpaper.

[0004] However, the application of existing technologies in complex working conditions still has obvious limitations; first, the substrate layer lacks flexibility design and is prone to local damage or breakage when bent, which makes it difficult for sandpaper to maintain structural integrity during curved surface grinding, especially prone to fatigue failure under dynamic loads; second, the traditional binder layer has insufficient high temperature resistance, and the accumulation of frictional heat during high-speed grinding will cause the binder to soften, which in turn causes the abrasive particles to fall off; third, although the abrasive layer achieves efficient cutting in a short period of time by increasing its hardness, its surface is prone to adhesion of abrasive chips, has poor anti-clogging ability, and rapidly decays grinding efficiency; in addition, although the single-layer coating design can provide certain wear protection, the coating adhesion and distribution uniformity are poor, resulting in uneven wear and even serious shedding during wet grinding. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides an anti-clogging and bending-resistant sandpaper and a preparation process thereof, which solves the problems of fracture failure caused by poor bending resistance of the base material layer of the sandpaper in the prior art, particle shedding caused by insufficient high temperature resistance of the adhesive layer, grinding efficiency attenuation caused by weak anti-clogging ability of the abrasive layer, and uneven wear of the single-layer coating design.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: an anti-clogging and anti-bending sandpaper, the sandpaper comprising a substrate layer, a binder layer, an abrasive layer and a surface coating, wherein: The substrate layer is made of a blended material of carbon fiber and aramid fiber, which is compounded with 0.5-1.5 parts of thermal conductive ceramic particles and 0.2-0.8 parts of shape memory alloy wire in a weight ratio of 2-5 parts; Carbon fiber has high strength and good thermal conductivity, while aramid fiber provides good flexibility and impact resistance. The two are blended to form a composite substrate, which provides excellent bending resistance while ensuring high strength. Thermally conductive ceramic particles (such as aluminum nitride or boron nitride) can form an efficient thermal conductivity path, allowing the heat generated during the grinding process to dissipate quickly, avoiding high temperature concentration and causing material performance degradation. After shape memory alloys (such as nickel-titanium alloys) are embedded in the substrate, fatigue damage to the material can be reduced during repeated bending, further extending the service life of the sandpaper; The adhesive layer is composed of 4-8 parts of modified acrylic resin, 0.1-0.3 parts of nanofiller and 1-2 parts of high thermal conductivity filler; acrylic has excellent flexibility and weather resistance, and can further improve its adhesion and high temperature resistance after modification. As a matrix material in the adhesive, it provides strong bonding of abrasive particles, and the high specific surface area of ​​nanomaterials (such as graphene or silicon dioxide) can improve the wear resistance and durability of the adhesive layer. At the same time, its excellent physical properties can improve the toughness and fatigue resistance of the adhesive layer. Finally, after adding high thermal conductivity fillers (such as boron nitride sheets), the thermal conductivity of the adhesive layer is greatly improved, and the grinding heat can be quickly directed to the substrate layer, so that the adhesive is not easy to soften or fall off due to high temperature; The abrasive layer comprises 5-10 parts of composite zirconium oxide particles and 0.5-1.0 parts of abrasive composite filler; Zirconia has extremely high hardness and wear resistance, and is suitable for efficient grinding. The surface of the zirconia particles treated by plasma forms a nano-scale hydrophobic coating, which can reduce the adhesion between particles and reduce the blockage caused by the adhesion of grinding chips. The abrasive composite filler (such as graphite or molybdenum disulfide) has self-lubricating properties, which can reduce the grinding friction coefficient and slow down the wear rate of abrasive particles, thereby improving grinding efficiency and the service life of sandpaper. The surface coating is composed of 1-2 parts of electroactive polymer and 0.3-0.8 parts of wear-resistant polymer material; Electroactive polymers (such as polyvinylidene fluoride-based polymers) can change surface properties under the action of an external electric field and actively repel the adhesion of wear chips. At the same time, their heat resistance and chemical stability make them suitable for high temperature and wet grinding conditions. Wear-resistant polymer materials (such as polyimide) form a wear-resistant protective layer with their high strength and antioxidant properties, delaying the loss of surface coatings.

[0007] Preferably, the substrate layer comprises: The carbon fiber and the aramid fiber are blended in a weight ratio of 2:1 to 5:1; This ratio ensures that the carbon fiber provides strength while giving full play to the flexibility of the aramid fiber, thus taking into account both strength and flexibility. The combination of the mechanical properties of the blended fibers achieves a balance between high strength and high flexibility, making the substrate suitable for the needs of complex curved surface processing. The thermally conductive ceramic particles are made of aluminum nitride or boron nitride; The addition of thermally conductive ceramic particles improves the thermal management capability of the substrate and reduces the impact of grinding heat accumulation on the overall structure; The shape memory alloy wire is a nickel-titanium alloy and is distributed inside the substrate; After the nickel-titanium alloy wire is embedded in the substrate, its memory effect can reduce fatigue stress when the sandpaper undergoes repeated bending, reduce the risk of material breakage, and thus improve the substrate's anti-bending performance.

[0008] Preferably, the adhesive layer comprises: The modified acrylic resin and the nanofiller are mixed in a weight ratio of 4:1 to 8:1; This ratio range can achieve a good balance between strength and flexibility, avoiding the brittle cracking of the adhesive due to excessive hardness or the reduction of bonding performance due to insufficient flexibility. The modified acrylic resin provides excellent flexibility and adhesion, and the nanofiller further improves the wear resistance and fatigue resistance by refining the adhesive structure. The nanofiller is graphene or silicon dioxide; Graphene or silica fillers enhance the interfacial bonding between the binder and the substrate and abrasive, ensuring the reliability of the sandpaper in high-temperature and high-speed grinding; The high thermal conductivity filler is a boron nitride sheet; High thermal conductivity fillers (boron nitride sheets) build efficient heat conduction channels in the binder layer to ensure that grinding heat is quickly dissipated and avoid binder decomposition or interface failure.

[0009] Preferably, the abrasive layer comprises: The surface of the composite zirconium oxide particles is plasma treated to form a nano-scale hydrophobic coating; Through the combination of plasma treatment and hydrophobic coating, the composite zirconium oxide particles not only retain the high hardness characteristics, but also form self-cleaning capabilities during the grinding process, avoiding clogging problems caused by abrasive chips or liquid adhesion. At the same time, the hydrophobic coating can also reduce frictional heat and extend the life of the abrasive layer; The abrasive composite filler includes graphite and molybdenum disulfide, mixed in a weight ratio of 1:1 to 2:1; This ratio can achieve the best balance between lubrication performance and durability under different working conditions. The synergistic effect of graphite and molybdenum disulfide can form a dynamic lubrication layer on the grinding surface, which can reduce the accumulation of grinding heat, reduce particle wear, and increase the service life of the abrasive layer. At the same time, its self-lubricating properties are particularly significant under high-speed grinding conditions.

[0010] Preferably, the surface coating comprises: The electroactive polymer is a polyvinylidene fluoride based polymer; Polyvinylidene fluoride-based polymers dynamically adjust the electric field distribution on the grinding surface through their electroactive response, forming an active chip removal mechanism, thereby significantly reducing the possibility of chip adhesion. Its electrochemical stability and heat resistance enable the coating to maintain anti-clogging performance under extreme conditions; The wear-resistant polymer material is polyimide; The wear resistance and high temperature resistance of polyimide ensure the physical integrity of the coating in long-term use. At the same time, its inert surface reduces the direct friction with the workpiece during the grinding process, improving the grinding efficiency of the sandpaper. The surface coating thickness is 1-2 μm and is formed by a multi-layer deposition process; This range can provide sufficient protection without significantly increasing the thickness of the sandpaper and affecting its flexibility. Through the multi-layer deposition process, the functional layers of the coating are more distinct, and the characteristics of each layer of material can be fully utilized. At the same time, the layer-by-layer deposition method reduces the accumulation of stress in the coating and reduces the risk of coating peeling under bending or high stress conditions.

[0011] The present invention also provides a preparation process of anti-blocking and bending-resistant sandpaper, comprising the following steps: S1, preparing a substrate layer; S2, coating an adhesive layer; S3, attached abrasive particles; S4, forming a surface coating; S5. Post-processing process.

[0012] Preferably, the preparation of the substrate layer comprises: The carbon fiber and the aramid fiber are mixed in a weight ratio of 2:1 to 5:1; Aramid fiber has high toughness and impact resistance, which can make up for the shortcomings of carbon fiber in bending and shearing performance. After the two fibers are mixed in proportion, a composite substrate with high strength and high flexibility is formed, which is suitable for complex curved surface processing scenarios; Add 0.5-1.5 parts of thermally conductive ceramic particles and 0.2-0.8 parts of shape memory alloy wire; Thermally conductive ceramic particles can build an efficient thermal conductive network inside the substrate, quickly transferring the heat generated during the grinding process to the substrate surface, thereby avoiding damage to the binder and abrasive layer caused by heat accumulation; the shape memory effect of the nickel-titanium alloy wire allows the substrate to automatically restore its original shape when repeatedly bent, thereby significantly reducing the risk of fracture or performance degradation caused by fatigue. This ratio ensures the flexibility and processing adaptability of the substrate while providing sufficient strength; Hot pressing compounding for 10-15 minutes at 150-180°C and 10-20MPa; High temperature and high pressure conditions promote the combination of fiber matrix, ceramic particles and shape memory alloy wire, so that the material forms a uniform and dense composite structure; during the hot pressing process, the molecular chain of the fiber will be rearranged at high temperature, enhancing the internal bonding force of the substrate and improving its comprehensive mechanical properties. This hot pressing parameter range ensures that a uniform composite substrate can be formed while avoiding high temperature damage to the mechanical properties of the fiber; laser direct writing technology is used to process the micropore array, with a pore size of 20-50μm, a pore spacing of 50-150μm, and a channel inclination of 30-60°; The presence of micropores provides a discharge channel for the chips generated during the grinding process, thereby effectively reducing blockage. The channel inclination design refers to the principles of fluid dynamics, optimizes the chip flow path, and ensures that the chips can quickly leave the working surface under the action of grinding force and pressure gradient.

[0013] Preferably, the coating adhesive layer comprises: Mix 4-8 parts of modified acrylic resin, 0.1-0.3 parts of nanofiller and 1-2 parts of high thermal conductive filler; As a matrix material, the modified acrylic resin provides high-strength bonding performance and excellent flexibility. By introducing heat-resistant groups into the molecular chain, its thermal stability is significantly improved, ensuring that the binder is not easy to decompose in a high temperature environment. This content range ensures that the resin has sufficient adhesion without excessively reducing the flexibility of the coating. The silica particles help reduce crack propagation and improve the mechanical stability of the coating by refining the microstructure of the binder. At the same time, the boron nitride flake structure forms a heat conduction channel in the binder, which improves the thermal conductivity of the coating, so that the heat generated during the grinding process is quickly transferred to the substrate layer for heat dissipation, avoiding the degradation of the binder performance caused by local high temperature; The adhesive is applied to the substrate surface by electrostatic spraying technology, with a coating thickness of 0.05-0.1mm; The coating thickness range is optimized to balance strength and flexibility. A coating that is too thin may not provide sufficient adhesion, while a coating that is too thick will affect the fixation of the abrasive particles and increase the overall hardness of the sandpaper. Pre-cure at 120-140℃ for 10-15 minutes; In the pre-curing stage, low-temperature heating is used to volatilize the solvent in the adhesive and initially form a cross-linked structure to improve the initial adhesion of the coating. This temperature range and time ensure that the adhesive has sufficient flexibility to avoid premature hardening that affects the bonding performance of subsequent processes. Final curing at 150-180℃ for 20-30 minutes; The final curing stage further accelerates the cross-linking reaction of the binder through high temperature, so that the coating can achieve the final physical and chemical properties. The increase in cross-linking degree significantly enhances the mechanical strength and high temperature resistance of the coating. The choice of this curing time ensures that the binder reacts completely while avoiding excessive heat treatment that causes material performance degradation.

[0014] Preferably, the attached abrasive particles include: Mixing 5-10 parts of composite zirconium oxide particles with 0.5-1.0 parts of abrasive composite filler; Through modified composite, the toughness of zirconium oxide particles is further improved, the possibility of particle breakage is reduced, and the service life of sandpaper is extended. Abrasive composite fillers (including graphite and molybdenum disulfide) as another self-lubricating material, especially in high temperature environment, show good lubrication performance, and synergize with graphite to form a dynamic lubrication layer, further optimizing the grinding performance of the abrasive layer. This range can achieve the best balance between grinding hardness and lubricity. The composite zirconium oxide particles are formed into a nano-scale hydrophobic coating by plasma treatment; The hydrophobic coating covers the particle surface by chemical deposition, reducing the adhesion between the particle and the liquid or grinding debris; this surface modification significantly improves the self-cleaning ability of the particle, allowing the grinding debris to quickly detach from the particle surface during the grinding process, thereby reducing clogging; Use electrostatic adsorption technology to evenly attach abrasive particles to the binder layer; Electrostatic adsorption technology uses the charge interaction between particles and substrates to firmly adsorb particles on the surface of the binder, which can avoid uneven distribution of particles or local accumulation, ensure the overall uniformity of the abrasive layer, and help improve the grinding accuracy and efficiency of sandpaper; Heat treatment at 200-220°C for 5-10 minutes; This heat treatment temperature optimizes the coating stability on the particle surface while avoiding the problem of excessively high temperature causing degradation of particle properties or softening of the binder layer. At the same time, this heat treatment time can fully ensure that the coating and binder are completely cured while avoiding material fatigue caused by excessive high temperature exposure time.

[0015] Preferably, the forming of the surface coating comprises: Prepare a mixed solution of 1-2 parts of electroactive polymer and 0.3-0.8 parts of wear-resistant polymer material; The ratio of electroactive polymer and wear-resistant polymer material can ensure that the coating achieves the best balance between functionality and mechanical properties; the hybrid coating is deposited on the surface of the abrasive layer by chemical vapor deposition (CVD) technology, and the coating thickness is 1-2μm; Chemical vapor deposition generates a coating on the substrate surface through chemical reactions, which can achieve uniform coverage at the atomic level, avoiding the uneven thickness problem in traditional spraying processes. This coating thickness ensures that the coating will not significantly increase the thickness of the sandpaper while providing functional protection, thereby avoiding affecting its flexibility and grinding performance; Curing at 80-100℃ for 1-2 hours; The curing process evaporates the residual solvent in the coating through low-temperature heating, while promoting the arrangement and cross-linking reaction of PVDF and polyimide molecular chains. The selection of this curing temperature and time range ensures that the coating has sufficient strength while avoiding premature aging or performance degradation of the coating due to high temperature.

[0016] The present invention provides an anti-clogging and anti-bending sandpaper and a preparation process thereof. It has the following beneficial effects: 1. The present invention adopts hot pressing and microporous array design of composite substrate layer, and realizes the balance between high strength and flexibility of substrate through blending of carbon fiber and aramid fiber, distribution of thermal conductive ceramic particles and embedding of shape memory alloy wire. Compared with the design of using only single fiber or common substrate in the prior art, the present invention significantly improves the bending resistance of sandpaper and solves the problem of easy fracture and fatigue failure of traditional sandpaper in complex curved surface processing.

[0017] 2. The present invention forms a bonding structure with both high adhesion and high heat dissipation performance through a modified acrylic adhesive layer reinforced by nanofillers and high thermal conductivity fillers. Compared with the solution of using only ordinary resin adhesive in the prior art, the present invention effectively reduces the phenomenon of softening and falling off of the adhesive due to heat accumulation during high-speed grinding, while improving the long-term adhesion performance of the abrasive, and solving the defect that the traditional sandpaper adhesive layer is not resistant to high temperatures.

[0018] 3. The present invention adopts a composite abrasive particle design with plasma treatment and hydrophobic coating, and successfully constructs an abrasive layer with self-cleaning ability through surface nano-level modification and electrostatic adsorption process. Different from the existing method of improving the grinding effect by relying solely on the hardness of particles, the present invention significantly reduces the probability of adhesion of grinding chips, achieves the technical effect of high grinding efficiency and anti-clogging, and overcomes the problem of grinding chip accumulation of traditional sandpaper in long-term use.

[0019] 4. The multifunctional surface coating design formed by the chemical vapor deposition process of the present invention, combined with the multi-layer deposition of electroactive polymers and wear-resistant polymer materials, provides dynamic chip removal capabilities and long-term wear protection. Compared with the simple protection method of single-layer coating in the prior art, the present invention significantly improves the anti-clogging and durability of the coating, especially under wet grinding and high-speed processing conditions, and solves the problem of easy shedding and insufficient durability of traditional coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Please see attached Figure 1 : Example 1: Preparation and performance optimization of composite substrate Mix carbon fiber and aramid fiber in a weight ratio of 3:1, and evenly disperse the mixed fibers to prevent agglomeration. Add 1 part of aluminum nitride thermal conductive ceramic particles to ensure that the particles are evenly distributed, and then add 0.4 parts of nickel-titanium alloy wire, cut into 5 mm short fibers, and evenly mix with the fibers.

[0023] The mixed material was placed in a hot press and pressed at 160°C and 15MPa for 12 minutes, and after cooling, a composite substrate with a thickness of 0.3 mm was formed, with a smooth surface and no exposed fibers.

[0024] Use laser direct writing equipment to process micropore arrays on the substrate surface. The pore size is controlled to be 30μm, the pore spacing is 100μm, and the inclination angle is 45°. Check the distribution of micropores to ensure that the number of micropores per square centimeter is uniform.

[0025] Example 2: Coating of a high thermal conductivity adhesive layer Weigh 6 parts of modified acrylic resin, add 0.2 parts of graphene nanofiller and 1.5 parts of boron nitride flakes, stir at 50°C for 30 minutes, and filter out impurities after mixing evenly.

[0026] The prepared adhesive solution is evenly coated on the surface of the substrate by electrostatic spraying equipment. The coating thickness is controlled to 0.08 mm, ensuring that the thickness of the edge and the center is consistent.

[0027] The coated substrate was placed in a preheating box and heated at 130°C for 12 minutes to initially cure the adhesive layer; then the temperature was raised to 170°C and maintained for 25 minutes to completely cure. The surface of the cured adhesive layer was observed to show no cracks or local uneven thickness.

[0028] Example 3: Preparation of anti-clogging abrasive layer Mix 8 parts of composite zirconium oxide particles with 0.7 parts of graphite and molybdenum disulfide in a weight ratio of 1:1. Stir for 15 minutes to ensure that the filler is evenly coated on the surface of the zirconium oxide particles.

[0029] The mixed abrasive particles were placed in a plasma treatment device and subjected to plasma flow for 10 minutes to form a nano-scale hydrophobic coating. The coating was uniform without any exposed particle surface.

[0030] Through electrostatic adsorption technology, the abrasive particles are evenly distributed on the surface of the binder layer, with a coverage rate of more than 95%. Then it is placed in a heat treatment box at 220℃ for 8 minutes to enhance the bonding strength between the particles and the binder.

[0031] Example 4: Formation of Dynamic Functional Surface Coating 1.5 parts of polyvinylidene fluoride (PVDF) and 0.5 parts of polyimide (PI) were weighed, dissolved in a solvent, and stirred at 50° C. for 2 hours to form a uniform solution.

[0032] The coating is deposited layer by layer on the sandpaper surface by chemical vapor deposition (CVD) technology. The first layer is a PVDF functional layer with a thickness of 0.5 μm; the second layer is a PI wear-resistant layer with a thickness of 0.8 μm; the last layer is a composite layer of PVDF and PI with a thickness of 0.6 μm, and the total thickness is 1.9 μm.

[0033] Place the coated sandpaper in a 90°C environment for 1.5 hours to allow the coating to stabilize. After cooling, check the coating to see if there is any peeling, wrinkling or cracking.

[0034] Example 5: Overall performance optimization and verification The substrate layer, the binder layer, the abrasive layer and the surface coating are assembled in the aforementioned process sequence to complete the overall preparation of the sandpaper.

[0035] Test the anti-bending performance of sandpaper. After bending the complex surface 2000 times, the sandpaper did not break or delaminate. Test the anti-clogging performance. During wet grinding, the grinding chips were discharged smoothly and there was no obvious clogging on the surface.

[0036] In high-speed rotating grinding equipment, at 200°C to simulate a high-temperature grinding environment, the sandpaper maintains stable performance without any binder softening or abrasive particle shedding.

[0037] Comparative Example 1: The substrate layer does not use shape memory alloy wire (corresponding to Example 1) The carbon fiber and aramid fiber were mixed in a weight ratio of 3:1, and 1 part of aluminum nitride thermal conductive ceramic particles was added, but no shape memory alloy wire was added. The mixture was directly stirred and dispersed evenly, and the fibers were chopped uniformly.

[0038] The composite substrate was prepared using the same hot pressing conditions (160°C, 15 MPa, 12 minutes), and the thickness was controlled at 0.3 mm.

[0039] As in Example 1, a micro-hole array was processed by laser direct writing, with a hole diameter of 30 μm, a hole spacing of 100 μm, and an inclination angle of 45°.

[0040] Comparative Example 2: No nanofiller added to the binder (corresponding to Example 2) A mixed solution of 6 parts of modified acrylic resin and 1.5 parts of boron nitride flakes was prepared without adding graphene nanofiller, and the stirring and mixing conditions remained unchanged.

[0041] The coating and thickness control were the same as in Example 2 (thickness 0.08 mm).

[0042] The pre-curing temperature and time (130°C, 12 minutes) and final curing conditions (170°C, 25 minutes) remained unchanged.

[0043] Comparative Example 3: Abrasive particles not treated with plasma (corresponding to Example 3) 8 parts of composite zirconium oxide particles were mixed with 0.7 parts of graphite and molybdenum disulfide in a ratio of 1:1 and used directly without plasma treatment.

[0044] According to the process of Example 3, the untreated abrasive particles were attached to the surface of the binder layer by electrostatic adsorption, and the heat treatment conditions remained the same (220° C., 8 minutes).

[0045] Comparative Example 4: Surface coating without CVD deposition process (corresponding to Example 4) Prepare a mixed solution of 1.5 parts of PVDF and 0.5 parts of polyimide, and stir evenly.

[0046] The coating material is applied to the sandpaper surface by a conventional spraying process, with a thickness controlled at 1-2 μm, and no layer-by-layer deposition is performed using CVD technology.

[0047] The curing conditions were the same as those in Example 4 (90° C., 1.5 hours).

[0048] Comparative Example 5: No electroactive polymer is added to the surface coating (corresponding to Example 4) Only 0.5 parts of polyimide solution was prepared without adding electroactive polymer PVDF, and the mixing and stirring method was the same as that of Example 4.

[0049] The coating process and curing conditions were kept the same as in Example 4, with a thickness of 1-2 μm.

[0050] Comparative Example 6: Hot Pressing Forming Parameters Not Optimized (Corresponding to Example 1) Carbon fiber and aramid fiber are mixed in a ratio of 3:1, and 1 part of aluminum nitride thermal conductive ceramic particles and 0.4 part of nickel-titanium alloy wire are added and mixed evenly.

[0051] The mixture was placed in a hot press, but the parameters were adjusted to 140°C, 8 MPa, and 8 minutes (the optimized high temperature and high pressure and extended time were not used).

[0052] The micro-hole processing method and size are consistent with those in Example 1.

[0053] Comparative Example 7: Surface coating without layered design (corresponding to Example 4) 1.5 parts of PVDF and 0.5 parts of polyimide are directly mixed into a single coating material without layered deposition design.

[0054] The coating was deposited in one pass by CVD technology with a thickness of 1.5 μm without multi-layer separation.

[0055] The curing temperature and time remained the same as in Example 4.

[0056] Comparative Example 8: Adhesive coating is not cured in stages (corresponding to Example 2) The binder solution (6 parts of modified acrylate resin, 0.2 parts of graphene nanofiller, 1.5 parts of Boron nitride sheet).

[0057] The electrostatic spray coating method and thickness control are the same as those in Example 2.

[0058] The coated substrate was directly placed at 170° C. for curing for 30 minutes without performing a staged curing process.

[0059] Experiment 1: Test of the bending resistance of the substrate layer Experimental procedures Sample preparation: According to the process of Example 1, a substrate layer containing shape memory alloy wires was prepared.

[0060] According to the process of Comparative Example 1, a substrate layer without shape memory alloy wire was prepared.

[0061] Both groups of samples were processed into 10×100 mm rectangular strips to ensure consistent size.

[0062] Experimental equipment: The test was carried out using a bending fatigue tester.

[0063] The test device fixes one end and bends the other end repeatedly within a 30° range.

[0064] Test setup: The bending angle was set to 30° and the frequency was 2 times / second.

[0065] Ten replicates of each set of samples were tested until the sample broke or completed 2000 bending cycles.

[0066] Data Records: The number of bends at which the sample breaks is recorded.

[0067] After the test, the sample surface was inspected to observe crack propagation and fatigue damage.

[0068] Experimental data of the bending resistance of the substrate layer Sample No. Test plan Bending times (times) Fracture state Surface damage degree 1 Example 1 1923 Partial break slight 2 Example 1 2000+ No break slight 3 Example 1 1867 Partial break slight 4 Example 1 2000+ No break Trace 5 Example 1 1992 No break slight 6 Comparative Example 1 983 Completely broken serious 7 Comparative Example 1 1220 Completely broken serious 8 Comparative Example 1 1135 Completely broken obvious 9 Comparative Example 1 1356 Partial break obvious 10 Comparative Example 1 1074 Completely broken serious The introduction of shape memory alloy wire significantly improves the bending resistance of the substrate layer. In the test, the samples of Example 1 still maintain good integrity after multiple bendings, and most of them can complete 2000 bending cycles. In contrast, the samples of Comparative Example 1 generally have a bending life of less than 1500 times due to the lack of reinforcement of shape memory alloy wire. This shows that the deformation recovery characteristics of the alloy wire play a key role in slowing down the expansion of fatigue damage; Further analysis shows that the shape memory alloy wire in Example 1 can absorb part of the load through the stress recovery effect during the bending process, reducing the accumulation of tensile stress between fiber layers. This property is particularly important in high-frequency bending and can significantly extend the fatigue life of the substrate. In contrast, due to the lack of a similar stress release mechanism, fatigue cracks in Comparative Example 1 rapidly expand in the initial stage, resulting in premature failure of the substrate; In addition, it was observed that the surface damage of the substrate in Example 1 was more minor, indicating that the shape memory alloy wire not only improved the bending resistance, but also dispersed the stress concentration area to a certain extent, slowing down the formation and expansion of local cracks. This is consistent with the mechanism proposed previously, proving that the shape memory alloy wire has irreplaceable functionality in the composite substrate.

[0069] Experiment 2: High temperature resistance test of adhesive layer Experimental procedures Sample preparation: Example 2: An adhesive layer (6 parts of modified acrylate resin, 0.2 parts of graphene nanofiller, 1.5 parts of boron nitride flakes) was prepared according to the process of Example 2, evenly coated on the surface of the substrate and cured.

[0070] Comparative Example 2: The sample was prepared according to the process of Comparative Example 2, except that no graphene nanofiller was added to the binder, and the other formulas and processes remained the same.

[0071] Experimental equipment: Using a high temperature heat treatment furnace, the temperature can be controlled accurately to ±2°C.

[0072] The surface and interface of the sample adhesive layer were observed using scanning electron microscopy (SEM).

[0073] Test conditions: The sample was placed in a furnace and the temperature was set to 200 °C for 30 min.

[0074] During the test, record the changes in the sample's appearance, especially whether the adhesive layer cracks, falls off, or produces bubbles.

[0075] Data Records: After the samples were taken out and cooled, the interface between the abrasive particles and the binder was examined using SEM.

[0076] The integrity of the adhesive layer surface was recorded, including crack length, distribution, and number of particles detached.

[0077] Experimental data of high temperature resistance of adhesive layer The experimental results reveal the importance of graphene nanofillers in the binder layer. The number of cracks in the sample of Example 2 is significantly less than that in Comparative Example 2, and the crack length is also greatly shortened. This shows that the introduction of graphene enhances the toughness and crack resistance of the binder layer and effectively inhibits crack propagation under high temperature conditions. However, due to the lack of nanofiller reinforcement, the binder of Comparative Example 2 quickly fails under thermal stress, and the crack generation and propagation speeds are significantly accelerated; The high specific surface area and two-dimensional sheet structure of graphene form a reinforced network in the binder, which not only improves the mechanical properties of the binder, but also provides an additional heat conduction path. Experiments show that the binder layer of Example 2 can still stably maintain its structural integrity at high temperatures. In contrast, the sample of Comparative Example 2 lacks an effective thermal stress dispersion mechanism, resulting in local overheating and softening of the binder, thereby exacerbating interface failure and particle shedding; In addition, the number of particles falling off in Example 2 is less, indicating that the addition of graphene filler also enhances the interfacial bonding force between the binder and the abrasive. This enhancement can be attributed to the buffering ability of graphene to interfacial stress, which effectively disperses the local stress around the particles under high temperature environment. In contrast, the interfacial bonding force of Comparative Example 2 is significantly weakened, and the particles are easily separated from the binder layer under the condition of uneven thermal expansion. The above phenomenon fully proves the key role of graphene nanofiller in improving the high temperature resistance of binder.

[0078] Experiment 3: Abrasive layer anti-clogging performance test Experimental procedures Sample preparation: Example 3: A composite zirconium oxide particle abrasive layer sandpaper after plasma treatment is prepared according to the process of Example 3 to form a nano-scale hydrophobic coating, which is electrostatically adsorbed on the binder layer.

[0079] Comparative Example 3: Sandpaper was prepared according to the process of Comparative Example 3, using composite zirconium oxide particles that were not treated with plasma, and other process conditions were the same.

[0080] Experimental equipment: Use a wet grinding test machine equipped with a steel plate grinding platform.

[0081] Scanning electron microscopy (SEM) was used to observe the abrasive particle surface and debris distribution.

[0082] Test conditions: The sample was fixed on a rotary grinding device, the rotation speed was set to 1000 rpm, and the loading pressure was 10N.

[0083] The grinding time was set to 20 min, and the grinding medium was water (5% lubricant volume ratio).

[0084] After the test, the amount of wear debris accumulation and the degree of clogging on the sandpaper surface were recorded.

[0085] Data Records: SEM was used to observe the adhesion of debris on the surface of sandpaper abrasive particles after grinding.

[0086] The wear debris coverage per unit area was recorded quantitatively.

[0087] Abrasive layer anti-clogging performance experimental data The test results clearly show that the sandpaper sample of Example 3 exhibits extremely low wear debris coverage under wet grinding conditions, and there is basically no large-scale accumulation on the surface of the abrasive particles. However, the wear debris coverage of the sample of Comparative Example 3 is significantly higher than double, and there is obvious blockage between particles. This difference shows that the nano-scale hydrophobic coating formed by plasma treatment plays an important role in the wear debris discharge process; The surface of the abrasive particles after plasma treatment has a micron-scale rough structure, which provides excellent hydrophobic properties, so that the liquid medium and grinding debris generated during the grinding process cannot stably adhere to the surface of the particles. In addition, the hydrophobic coating reduces the surface energy between the particles, and the grinding debris is more easily removed under the action of mechanical force. This phenomenon is fully reflected in Example 3, where the sandpaper surface is evenly stacked and the thickness is extremely small, further reducing the grinding resistance; Since the comparative example 3 has not been surface treated, the particle surface is relatively smooth and has strong hydrophilicity, and the grinding debris and liquid medium easily form a pile layer between the particles, resulting in local blockage. This blockage directly reduces the grinding efficiency of the sandpaper and increases the risk of grinding heat accumulation. The comparative data show that the modified process of Example 3 successfully solves the problem of insufficient anti-blocking performance of traditional abrasive particles, especially in wet grinding, which has significant advantages.

[0088] Experiment 4: Surface coating wear resistance test Experimental procedures Sample preparation: Example 4: According to the process of Example 4, chemical vapor deposition (CVD) technology is used to deposit electroactive polymers and wear-resistant polymer materials layer by layer to form a multi-layer composite coating with a total coating thickness of 1.9 μm.

[0089] Comparative Example 4: A single-layer coating was prepared by spraying process, with a coating thickness of 1.5 μm. The remaining materials and curing process were consistent with those in Example 4.

[0090] Experimental equipment: The wear resistance of the coating was tested using a rotating disc abrasion tester.

[0091] Equipped with a 3D profilometer to measure coating wear depth.

[0092] Test conditions: The sample was fixed under a rotating grinding disc with a diameter of 100 mm and a rotation speed of 1000 rpm.

[0093] The grinding pressure was set to 20 N and the duration was 20 min.

[0094] The surface thickness change and the smoothness of the worn area of ​​each group of samples before and after the test were recorded.

[0095] Data Records: The depth and surface area of ​​the worn area were measured using a 3D profilometer.

[0096] Qualitative evaluation of the wear uniformity and residual adhesion of the coating.

[0097] Surface coating wear resistance test data The test results show that the multilayer coating sample in Example 4 has a significant wear resistance advantage. Its wear depth is always kept within 0.2μm, and the coating adhesion rate is close to more than 95%, while the single-layer coating of Comparative Example 4 shows severe wear characteristics. This difference highlights the significant improvement of the wear resistance of the coating by the multilayer deposition design, especially under high pressure and high speed grinding conditions, the uniformity and stability of the CVD process are particularly critical; The layered design of the multilayer coating makes its internal functions independent of each other. The electroactive polymer dynamically adjusts the surface charge distribution in the outer layer, reducing the generation of frictional heat; the wear-resistant polymer material forms a physical barrier in the middle layer, significantly enhancing the anti-scratch ability. In contrast, the single-layer coating of Comparative Example 4 failed to achieve the layered function, and various properties were concentrated in a single material, resulting in the inability to effectively disperse the grinding stress, which ultimately accelerated the wear of the coating; In addition, the advantage of the CVD process is its atomic-level deposition accuracy, which ensures the consistency of coating thickness and uniform distribution of adhesion. The sample of Example 4 showed almost no significant uneven wear in the wear area, and this stability is difficult to achieve with the traditional spraying process. The sample of Comparative Example 4 showed coating shedding during grinding, which further verified the reliability of the CVD process under complex working conditions. These results fully illustrate the creativity and superiority of the surface coating process of this technical solution.

[0098] Experiment 5: Comprehensive polishing performance test Experimental procedures Sample preparation: Examples 1-4: Complete sandpaper samples based on a composite substrate, a binder layer, plasma-treated abrasive grains and a CVD multi-layer coating were prepared according to the aforementioned process.

[0099] Comparative Examples 1-4: Sandpaper samples without shape memory alloy wire, nanofiller, untreated abrasive particles and single-layer coating were prepared according to the process of the comparative examples.

[0100] Experimental equipment: Use a high-speed rotary grinder equipped with an aluminum alloy grinding platform.

[0101] A wet grinding device was added to the experiment, and the grinding medium was 5% water-based lubricating fluid.

[0102] Test conditions: Dry working condition: apply pressure of 10N, speed of 1500rpm, set the grinding time to 10 minutes, and record the grinding depth and sandpaper wear.

[0103] Wet working condition: the same pressure and speed for 15 minutes, and record the degree of abrasive accumulation and the service life of the sandpaper.

[0104] Data Records: Grinding efficiency is calculated as grinding depth (mm) / time (min).

[0105] The surface wear of sandpaper was measured using a 3D profilometer.

[0106] Qualitatively record the wear debris accumulation and the durability of the sandpaper.

[0107] Comprehensive grinding performance test data The experimental data clearly reveal the difference in comprehensive grinding performance between the embodiments and the comparative examples under dry and wet conditions. The sandpaper samples of embodiments 1-4 show significant advantages in grinding efficiency, wear amount, and degree of accumulation of abrasive debris. Especially in wet grinding, the service life of the sandpaper of the embodiments generally exceeds 70 minutes, while the comparative examples only fail within 30-40 minutes, highlighting the improvement effect of the technical solution.

[0108] The addition of shape memory alloy wire is the key to improving the performance of the substrate layer. It delays fatigue damage of the substrate through stress recovery mechanism under bending and dynamic load, which not only improves the grinding strength under dry conditions, but also further ensures the mechanical stability of sandpaper under wet conditions. Due to the lack of similar design, the bending part of comparative example 1 is easy to break during grinding, resulting in a significant decrease in grinding efficiency.

[0109] The multi-layer coating is particularly effective in preventing wear debris accumulation and resisting wear. The sandpaper sample of Example 4 exhibits excellent anti-clogging performance under the coating uniformity and layering function guaranteed by CVD technology. Even in wet working conditions, the adhesion and durability of the coating remain stable. However, the single-layer coating of Comparative Example 4 causes serious clogging on the sandpaper surface due to uneven wear and partial shedding, further accelerating the failure rate of the sandpaper.

[0110] The experiment also showed that the abrasive particles treated with plasma had obvious self-cleaning function. The sandpaper of the embodiment can quickly remove the grinding debris, while the abrasive layer of the comparative example produced a large amount of accumulation during wet grinding, which directly affected the grinding efficiency. This is completely consistent with the mechanism proposed before, which fully proves the reliability of this technical solution under complex working conditions.

[0111] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An anti-clogging and anti-bending sandpaper, characterized in that: The sandpaper comprises a substrate layer, a binder layer, an abrasive layer and a surface coating, wherein: The substrate layer is made of a blended material of carbon fiber and aramid fiber, which is compounded with 0.5-1.5 parts of thermal conductive ceramic particles and 0.2-0.8 parts of shape memory alloy wire in a weight ratio of 2-5 parts; The adhesive layer is composed of 4-8 parts of modified acrylate resin, 0.1-0.3 parts of nano filler and 1-2 parts of high thermal conductivity filler; The abrasive layer comprises 5-10 parts of composite zirconium oxide particles and 0.5-1.0 parts of abrasive composite filler; The surface coating is composed of 1-2 parts of electroactive polymer and 0.3-0.8 parts of wear-resistant high molecular material.

2. The anti-clogging and anti-bending sandpaper according to claim 1, characterized in that: The substrate layer comprises: The carbon fiber and the aramid fiber are blended in a weight ratio of 2:1 to 5:1; The thermally conductive ceramic particles are made of aluminum nitride or boron nitride; The shape memory alloy wire is a nickel-titanium alloy and is distributed inside the substrate.

3. The anti-clogging and anti-bending sandpaper according to claim 1, characterized in that: The adhesive layer comprises: The modified acrylic resin and the nanofiller are mixed in a weight ratio of 4:1 to 8:1; The nanofiller is graphene or silicon dioxide; The high thermal conductivity filler is boron nitride flakes.

4. The anti-clogging and anti-bending sandpaper according to claim 1, characterized in that: The abrasive layer comprises: The surface of the composite zirconium oxide particles is plasma treated to form a nano-scale hydrophobic coating; The abrasive composite filler includes graphite and molybdenum disulfide, which are mixed in a weight ratio of 1:1 to 2:

1.

5. The anti-clogging and anti-bending sandpaper according to claim 1, characterized in that: The surface coating comprises: The electroactive polymer is a polyvinylidene fluoride based polymer; The wear-resistant polymer material is polyimide; The surface coating has a thickness of 1-2 μm and is formed by a multi-layer deposition process.

6. A process for preparing anti-clogging and bending-resistant sandpaper, characterized in that: The use of the anti-clogging and bending-resistant sandpaper according to any one of claims 1 to 5 comprises the following steps: preparing a substrate layer; applying an adhesive layer; Attached abrasive particles; forming a surface coating; Post-processing process.

7. The process for preparing the anti-clogging and bending-resistant sandpaper according to claim 6, characterized in that: The preparation of the substrate layer comprises: The carbon fiber and the aramid fiber are mixed in a weight ratio of 2:1 to 5:1; Add 0.5-1.5 parts of thermally conductive ceramic particles and 0.2-0.8 parts of shape memory alloy wire; Hot pressing compounding for 10-15 minutes at 150-180°C and 10-20MPa; The microhole array is processed using laser direct writing technology, with a pore diameter of 20-50μm, a pore spacing of 50-150μm, and a pore inclination of 30-60°.

8. The process for preparing the anti-clogging and anti-bending sandpaper according to claim 6, characterized in that: The coating adhesive layer comprises: Mix 4-8 parts of modified acrylate resin, 0.1-0.3 parts of nanofiller and 1-2 parts of high thermal conductive filler; The adhesive is applied to the substrate surface by electrostatic spraying technology, with a coating thickness of 0.05-0.1mm; Pre-cure at 120-140℃ for 10-15 minutes; Final curing at 150-180℃ for 20-30 minutes.

9. The process for preparing the anti-clogging and anti-bending sandpaper according to claim 6, characterized in that: The attached abrasive particles include: Mixing 5-10 parts of composite zirconium oxide particles with 0.5-1.0 parts of abrasive composite filler; The composite zirconium oxide particles are formed into a nano-scale hydrophobic coating by plasma treatment; Use electrostatic adsorption technology to evenly attach abrasive particles to the binder layer; Heat treatment at 200-220°C for 5-10 minutes.

10. The process for preparing the anti-clogging and anti-bending sandpaper according to claim 6, characterized in that: The forming of the surface coating comprises: Prepare a mixed solution of 1-2 parts of electroactive polymer and 0.3-0.8 parts of wear-resistant polymer material; The mixed coating is deposited on the surface of the abrasive layer by chemical vapor deposition technology, and the coating thickness is 1-2 μm; Curing at 80-100℃ for 1-2 hours.